Experimental measurements of the hydrodynamic performance and structural loading of the Transverse Horizontal Axis Water Turbine: Part 1 - McAdam, R; Houlsby, G; Oldfield, M (2013)
This paper is the first of three, which outline the procedures and results for a set of experiments carried out on various configurations of the Transverse Horizontal Axis Water Turbine (THAWT), which is a horizontally orientated variant of the Darrieus cross-flow turbine. Tests were conducted in the combined wind, wave and current tank at Newcastle University on a 0.5 m diameter rotor, while the flow depth and velocity were varied over a range of realistic Froude numbers for tidal streams. Various configurations of the device were tested to assess the merits of varied blade pitch, rotor solidity, blockage ratio and truss oriented blades. Experiments were carried out using a speed controlled motor/generator, allowing quasi-steady results to be taken over a range of tip speed ratios. Measurements of power, thrust, blade loading and free surface deformation provide extensive data for future validation of numerical codes and demonstrate the ability of the device to exceed the Lanchester-Betz limit for kinetic efficiency by using high blockage. This paper covers the experimental procedures and results for the hydrodynamic performance for the parallel bladed variant of the THAWT device. The second paper covers the hydrodynamic loading of the parallel bladed rotor and the third covers both hydrodynamic performance and loading of the truss configured THAWT device. © 2013 Elsevier Ltd.